2019
DOI: 10.1037/xge0000483
|View full text |Cite
|
Sign up to set email alerts
|

From simple to complex actions: Response–response bindings as a new approach to action sequences.

Abstract: Binding between stimulus features and between stimuli and responses has been discussed as a central mechanism in human action control: Carrying out a response to a stimulus leads to bindings between stimulus and response features, so that repetition of one can retrieve the other later on. We find it intriguing that all discussions to date focus either on stimulus-stimulus or on stimulus-response bindings. Here we argue that response-response bindings are equally relevant for action control, if binding really p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 62 publications
2
60
0
Order By: Relevance
“…Targetresponse bindings are still measurable after four seconds following integration (Hommel & Colzato, 2004) and have been shown to completely decay within five to six seconds . Response-effect bindings (Herwig & Waszak, 2012) and also bindings between individually planned and executed responses (Moeller & Frings, 2019) were even reported after a delay of six seconds. If the decay function of bindings is generally related with beta ERS, we would expect a similar correlation between binding effects and beta ERS as found in the present study either for longer or for later time windows regarding target or effect stimuli.…”
Section: Dicsmentioning
confidence: 92%
“…Targetresponse bindings are still measurable after four seconds following integration (Hommel & Colzato, 2004) and have been shown to completely decay within five to six seconds . Response-effect bindings (Herwig & Waszak, 2012) and also bindings between individually planned and executed responses (Moeller & Frings, 2019) were even reported after a delay of six seconds. If the decay function of bindings is generally related with beta ERS, we would expect a similar correlation between binding effects and beta ERS as found in the present study either for longer or for later time windows regarding target or effect stimuli.…”
Section: Dicsmentioning
confidence: 92%
“…It has been suggested that event representation can be hierarchically structured. Not only are microevents of a single response represented via bindings of their elements (i.e., SR bindings), but the same micro-events may also be integrated in larger-scale representations (see Hommel et al, 2001;Moeller & Frings, 2019a, b, for a similar view regarding the representation of task pairs: Hirsch, Nolden, & Koch, 2017). From this perspective, each Response A and B in our study can be understood as one micro-event, which were integrated with each other in a larger-scale representation for each prime.…”
Section: Discussionmentioning
confidence: 99%
“…Participants The effect sizes of RR-binding effects [computed as t/sqrt(n)] were large (0.77) on average in former studies (Moeller & Frings, 2019a, b). If RR integration is not impaired by an effector switch, we therefore expected to find an effect of d = 0.77.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations